The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/01677063.2013.800060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Neural Bases for Species-Specific Behavior inDrosophilaSpecies

Abstract: Behavioral changes in evolution have attracted the attention of many evolutionary biologists. Closely related species, or even individuals from different populations within a species, often exhibit remarkably different behaviors. Such behavioral diversification has been implicated as a cause of speciation in some cases, yet the mechanisms that produce and maintain these changes remain largely unknown. Drosophila melanogaster, an outstanding model organism with which to explore the causal link among the gene, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…Naturally occurring variants affecting behavioral traits are of particular interest because of their potential contribution to the behavioral differences that have emerged in the evolution of closely related species and, in some cases, may have even contributed to speciation (Yamamoto and Ishikawa 2013). For example, latitudinal variation in the length of a Thr-Gly repeat in the Per protein in D. melanogaster is inferred to reflect an important role in thermal adaptation (Sawyer et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring variants affecting behavioral traits are of particular interest because of their potential contribution to the behavioral differences that have emerged in the evolution of closely related species and, in some cases, may have even contributed to speciation (Yamamoto and Ishikawa 2013). For example, latitudinal variation in the length of a Thr-Gly repeat in the Per protein in D. melanogaster is inferred to reflect an important role in thermal adaptation (Sawyer et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have identified differences in specific behaviors, such as courtship behavior, between these species [14,16,32,33], here we assayed the full repertoire of behaviors the flies performed in the arena, with the aim of identifying combinations of behaviors that may be evolving together. To measure this repertoire, we used a previously-described behavior mapping method [19,22] that starts from raw video images and attempts to find each animals stereotyped movements in an unsupervised manner.…”
Section: Experiments and Behavioral Quantificationmentioning
confidence: 99%
“…Variable behaviors and rapid behavioral evolution likely allows species to adapt rapidly to new or varying environments [3,4]. Despite the importance of animal behavior, progress in revealing the genetic basis of behavioral evolution has been slow [5][6][7][8]. In contrast, recent decades have seen significant progress in understanding the genetic causes of morphological evolution [9][10][11][12].…”
mentioning
confidence: 99%
“…Song is not restricted to males, and in some clades male-female duets are an important aspect of courtship (Satokangas et al 1994). The courtship song of D. melanogaster has been extensively studied with more than a dozen genes identified as contributing to song (Gleason 2005;Yamamoto and Ishikawa 2013). In contrast, only a few loci have been identified that also affect reproductive isolation.…”
Section: Prezygotic Isolationmentioning
confidence: 99%